Investigating the Effects of Biochar Electrode Macrostructure and Dimension on Electrical Double-Layer Capacitor Performance. Issue 2 (1st January 2018) - Yanchus, Daniel A.; Kirk, Donald W.; Jia, Charles Q.
Abstract : This study investigates biochar supercapacitor electrodes made several times larger than those in commercial application, using both thick monolithic and powder thin film structures. Slow-pyrolysis of wood precursors produces carbonized biochar monoliths which retain the internal structures of biomass. While this natural network of transportation channels for water and nutrients was not found to facilitate ion migration in capacitive charge/discharge cycles, monolithic electrodes revealed lower intrinsic resistances than thin films containing PTFE binder. As a consequence, monolithic electrodes up to 5 mm thick show equivalent specific capacitance performance to their thin film counterparts. This feature could allow greater energy density storage per device.